Application of The Contextual Teaching Learning Model in Pancasila Education Subject Using Virtual Reality Technology - Lesmana, Tebi; Bestari, Prayoga; Fitriasari, Susan; Afriansyah, Ardi (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2025)
This research aims to explore the application of contextual learning models in learning Pancasila Education by utilizing Virtual Reality (VR) technology. The contextual approach is chosen because it is believed able to increase student understanding and engagement through relevant and meaningful learning experiences. The method in this research is using literature study, which involves collecting and analyzing data from various written sources, such as books, scientific journals, articles, and other publications, to gain an in-depth understanding of the topic under study and identify relevant trends and findings. The results show that the use of contextual learning models combined with VR technology can increase student learning motivation, material understanding, and critical thinking skills. Students feel more involved and enthusiastic in the learning process because they can interact directly with the material content through VR simulation. The challenges for implementation is limited access to VR technology, particularly in schools located in remote areas or those with insufficient financial resources. Also designing appropriate and engaging learning materials that align with the curriculum and students' cognitive levels is the major obstacle for implementation. The findings suggest that the integration of VR technology in Pancasila Education learning can be an effective alternative to create a more dynamic and immersive learning experience. It is hoped that this research can be a reference for educators in developing innovative learning strategies that are in accordance with technological developments and educational needs.